Apoyo a la Secretaría de Planeación y Desempeño Institucional en la revisión y seguimiento de proyectos civiles en el municipio de Nobsa, Boyacá - Palencia Sánchez, Claudia Bibiana (Universidad Antonio Nariño, 2022)
In this internship, several activities were carried out in support of the Office of Planning and Institutional Performance of the Mayor's Office of Nobsa, such as review and monitoring of projects, preparation of technical proposals, control and monitoring of works, progress of work, inspection visits of different works that the municipality has, among others named in the daily logs, allowing me to grow as a professional. Several supervision visits were made to the sports complexes that the municipality has to improve them. The purpose of the internship is to be the technical support to supply the supervision and followup that these activities require, since not having this personnel implies a waste of time in the formulation of projects and their management, making a contribution for the improvement of the processes mentioned above.